MYB46 integrates cuticle and cell wall remodeling to coordinate drought tolerance and pathogen resistance in Arabidopsis - Jin, Shurong (The New phytologist, 2025)
© 2025 The Author(s). New Phytologist © 2025 New Phytologist Foundation.